Secondary cell

JP2025032623APending Publication Date: 2025-03-12TOYOTA BATTERY CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
JP2023138012
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-08-28
Publication Date
2025-03-12

AI Technical Summary

Benefits of technology

【0009】 本発明によれば、電池性能の向上を図ることができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025032623000001_ABST
    Figure 2025032623000001_ABST
Patent Text Reader

Abstract

To improve cell performance.SOLUTION: A secondary cell having constitution as a lithium ion secondary cell includes a negative active material layer disposed over a substrate, and an electrode sheet as a negative electrode plate, the electrode sheet has a coat 50 covering a surface 32s of the negative active material layer. An electrolyte impregnated into the electrode sheet includes a sulfur-based additive. When a thickness area δ from an electrolyte solution interface 50s of the coat 50 up to the depth of 5 nm is defined as an electrolyte-solution-side region δ1 and a thickness region δ deeper than the electrolyte-solution-side region δ1 is defined as an electrolyte-solution-side region δ2. In the secondary cell, a ratio of the amount of sulfur component α included in the electrolyte-solution-side region δ1 to the amount of sulfur component α included in the electrolyte-solution-side region δ2 is 0.58 or more and 0.84 or less.SELECTED DRAWING: Figure 5
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a secondary battery. [Background technology]

[0002] Conventionally, some secondary batteries such as lithium ion secondary batteries contain a sulfur-based additive in their electrolyte solution. For example, Patent Documents 1 and 2 disclose that a coating containing a sulfur component is formed on the surface of the negative electrode active material layer on the negative electrode side of the secondary battery.

[0003] That is, such a coating formed at the electrolyte interface on the negative electrode side is called "SEI (Solid Electrolyte Interphase)". This coating is mainly formed when the electrolyte is decomposed at the interface between the negative electrode and the electrolyte during charging of the secondary battery. Furthermore, by including a sulfur-based additive in the electrolyte, the coating contains a sulfur component. This can improve the battery performance. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] JP 2014-127313 A [Patent Document 2] International Publication No. 2022 / 059557 Summary of the Invention [Problem to be solved by the invention]

[0005] However, in applications requiring high levels of battery performance, such as electric vehicles, further improvements in performance are being sought on a daily basis, and therefore further improvements are being sought in the above-mentioned conventional technologies in order to meet the evolving requirements. [Means for solving the problem]

[0006] Various aspects of the secondary battery that solves the above problems will be described below. Aspect 1 is a secondary battery including a negative electrode plate having a negative electrode active material layer laminated on a substrate and a coating covering a surface of the negative electrode active material layer, and an electrolyte impregnated in the negative electrode plate contains a sulfur-based additive, wherein a thickness region of the coating from the electrolyte interface to a depth of 5 nm is defined as an electrolyte interface side region, and the thickness region deeper than the electrolyte interface side region is defined as an active material surface side region, and the ratio of the amount of sulfur component contained in the active material surface side region to the amount of sulfur component contained in the electrolyte interface side region is 0.58 or more and 0.84 or less.

[0007] According to the above-mentioned configuration, the effect of improving the battery performance due to the coating containing a sulfur component can be enhanced. In particular, the rate of deterioration of the battery capacity can be reduced. As a result, the secondary battery can be used for a longer period of time.

[0008] A second embodiment is the secondary battery of the first embodiment, which contains lithium fluorosulfonate and lithium methanesulfonate as the sulfur-based additive. That is, by adding sulfur-based additives having different reduction potentials to the electrolyte, and adjusting the amounts of these additives, it is possible to easily control the ratio of the amount of sulfur component contained in the active material surface side region to the amount of sulfur component contained in the electrolyte interface side region, and thereby it is possible to set the ratio of the amount of sulfur component contained in the electrolyte interface side region and the active material surface side region to a suitable range, thereby improving the battery performance. Effect of the Invention

[0009] According to the present invention, it is possible to improve the battery performance. [Brief description of the drawings]

[0010] [Figure 1] FIG. 1 is a perspective view of a secondary battery. [Diagram 2] FIG. 2 is an exploded view of the electrode assembly. [Diagram 3]FIG. 3 is a side view of the secondary battery. [Figure 4] FIG. 4 is a cross-sectional view of the coating (SEI) covering the surface of the negative electrode active material. [Diagram 5] FIG. 5 is a graph showing the distribution of sulfur components contained in the coating. [Figure 6] FIG. 6 is a table showing the test results of the secondary batteries. [Figure 7] FIG. 7 is a graph showing the distribution of sulfur components contained in the coating of each test specimen. [Figure 8] FIG. 8 is a graph showing the capacity retention rate after the storage deterioration test was performed on each test specimen. [Figure 9] FIG. 9 is a graph in which the relationship between the sulfur content ratio and the rate of capacity deterioration is plotted on an orthogonal coordinate system. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0011] Hereinafter, an embodiment of a secondary battery will be described with reference to the drawings. (Lithium-ion secondary battery) 1, the secondary battery 1 includes an electrode assembly 10 in which a positive electrode 3, a negative electrode 4, and a separator 5 are integrated, and a case 20 that houses the electrode assembly 10. The secondary battery 1 of this embodiment has a configuration as a lithium ion secondary battery in which the electrode assembly 10 in the case 20 is impregnated with a non-aqueous electrolyte solution (not shown).

[0012] More specifically, in the secondary battery 1 of this embodiment, the positive electrode 3, the negative electrode 4, and the separator 5 are laminated with a sheet-like outer shape. Then, by winding up the laminate of the positive electrode 3, the negative electrode 4, and the separator 5, an electrode body 10 is formed in which the positive and negative electrodes and the separators 5 are alternately arranged in the radial direction with the separator 5 sandwiched between the positive electrode 3 and the negative electrode 4.

[0013] The case 20 of this embodiment includes a case body 21 having a flat, substantially rectangular box shape, and a lid member 22 that closes an open end 21x of the case body 21. The electrode body 10 of this embodiment has a flat outer shape that corresponds to the box shape of the case 20.

[0014] (Electrode sheet and electrode body) More specifically, as shown in FIG. 2, in the secondary battery 1 of this embodiment, the positive electrode 3 and the negative electrode 4 each have a configuration as an electrode sheet 35 including a current collector 31 having a sheet-like outer shape and an electrode active material layer 32 laminated on this current collector 31.

[0015] Specifically, for the electrode sheet 35P for the positive electrode 3, an electrode mixture containing lithium transition metal oxide as a positive electrode active material, i.e., a composite paste 37P as a positive electrode mixture, is applied to a substrate 36P made of aluminum or the like that constitutes the positive electrode current collector 31P. For the electrode sheet 35N for the negative electrode 4, an electrode mixture in the form of a slurry containing a carbon-based material that serves as a negative electrode active material, i.e., a composite paste 37N as a negative electrode mixture, is applied to a substrate 36N made of copper or the like that constitutes the negative electrode current collector 31N. Furthermore, each of these composite pastes 37P and 37N contains a binder. In the secondary battery 1 of this embodiment, the composite pastes 37P and 37N are dried to form the corresponding positive electrode active material layer 32P and negative electrode active material layer 32N on the positive and negative electrode sheets 35P and 35N, respectively.

[0016] Furthermore, in the secondary battery 1 of this embodiment, the positive and negative electrode sheets 35P, 35N are each shaped into a belt-like shape. The electrode body 10 of this embodiment has a configuration as a wound body in which the positive and negative electrode sheets 35P, 35N, which are stacked with the separator 5 sandwiched therebetween, are wound around a winding axis 10x extending in the width direction of the belt-like shape (the left-right direction in FIG. 2).

[0017] 2, the separator 5 and each electrode sheet 35 are wound in such a manner that the electrode sheet 35P constituting the positive electrode 3 is wound inward. However, this figure is one example showing the structure of the electrode body 10, and the separator 5 and each electrode sheet 35 may be wound in such a manner that the electrode sheet 35N constituting the negative electrode 4 is wound inward. This determines whether the electrode sheet 35 arranged on the outermost shell of the electrode body 10 is the electrode sheet 35P constituting the positive electrode 3 or the electrode sheet 35N constituting the negative electrode 4.

[0018] 1 to 3, the cover member 22 of the case 20 is provided with a positive electrode terminal 38P and a negative electrode terminal 38N that protrude to the outside of the case 20. Furthermore, each electrode sheet 35 has an uncoated portion 39 in which the electrode active material layer 32 is not formed on the current collector 31. The secondary battery 1 of this embodiment is configured such that, by utilizing these uncoated portions 39, the electrode sheet 35P constituting the positive electrode 3 and the positive electrode terminal 38P are electrically connected, and the electrode sheet 35N constituting the negative electrode 4 and the negative electrode terminal 38N are electrically connected.

[0019] Specifically, the electrode body 10 of this embodiment is housed in the case 20 with its winding axis 10x aligned along the longitudinal direction (left-right direction in FIG. 1) of the cover member 22, which is an elongated, generally rectangular plate. Furthermore, in this state, an uncoated portion 39P of an electrode sheet 35P constituting the positive electrode 3 is connected to a positive electrode terminal 38P via a connecting member 40P. Similarly, an uncoated portion 39N of an electrode sheet 35N constituting the negative electrode 4 is connected to a negative electrode terminal 38N via a connecting member 40N.

[0020] Furthermore, an electrolyte solution 45 is injected into the case 20. That is, the electrolyte solution 45 of the secondary battery 1 having a configuration as a lithium ion secondary battery is one in which a lithium salt serving as a supporting salt is dissolved in an organic solvent. Thus, the secondary battery 1 of this embodiment is configured such that the electrode body 10 sealed in the case 20 is impregnated with the electrolyte solution 45.

[0021] (SEI film and distribution of sulfur components contained therein) As shown in FIG. 4, the secondary battery 1 of this embodiment having a configuration as a lithium ion secondary battery has a coating 50 covering the surface 32s of the negative electrode active material layer 32N. That is, this coating 50 is called "SEI (Solid Electrolyte Interphase)". In addition, this coating 50 is mainly formed by decomposition of the electrolyte 45 at the interface between the negative electrode active material layer 32N of the electrode sheet 35N constituting the negative electrode plate 52N and the electrolyte 45, that is, at the electrolyte interface 50s, during charging of the secondary battery 1. Furthermore, in the secondary battery 1 of this embodiment, the electrolyte 45 contains a sulfur-based additive 60. Thus, the secondary battery 1 of this embodiment contains a sulfur component S in the coating 50.

[0022] 4 and 5, the secondary battery 1 of this embodiment has a coating 50 with a thickness d, and a thickness region δ of the coating 50 is represented by a depth D with the electrolyte interface 50s defined as "0". In this case, the coating 50 contains more sulfur components S in a portion of the thickness region δ closer to the electrolyte interface 50s.

[0023] Specifically, the thickness region δ of the coating 50 from the electrolyte interface 50s to a depth D of 5 nm is defined as the electrolyte interface side region δ1. The thickness region δ deeper than the electrolyte interface side region δ1 is defined as the active material surface side region δ2. In other words, if the depth D of the surface 32s of the negative electrode active material layer 32N corresponding to the thickness d of the coating 50 is defined as "Dx", the thickness region δ from the depth D of "5 nm" to "Dx" is the active material surface side region δ2. In this case, the coating 50 contains a larger amount of sulfur component S in the electrolyte interface side region δ1 than in the active material surface side region δ2.

[0024] That is, when the secondary battery 1 is charged, the coating 50 grows on the surface 32s of the negative electrode active material layer 32N. In other words, the thickness d of the coating 50 increases, and the electrical resistance of the coating 50 increases. This in turn reduces the electrode potential at the electrolyte interface 50s. When the electrode potential at the electrolyte interface 50s becomes lower than the reduction potential of sulfur, the coating 50 contains the sulfur component S.

[0025] In addition, in the portion close to the electrolyte interface 50s in the thickness region δ, the thickness region δ from the electrolyte interface 50s to a depth D of 5 nm tends to contain more sulfur components S, regardless of the thickness d of the coating 50. In light of this, as described above, the thickness region δ of the coating 50 is divided into an electrolyte interface side region δ1 and an active material surface side region δ2. Furthermore, the contents of the sulfur components S contained in the electrolyte interface side region δ1 and the active material surface side region δ2, that is, the sulfur component amount α (wt%), are compared. Thus, the secondary battery 1 of this embodiment is configured so that the ratio of the sulfur component amount α contained in the active material surface side region δ2 to the sulfur component amount α contained in the electrolyte interface side region δ1 is 0.58 or more and 0.84 or less.

[0026] Specifically, the sulfur content α in the coating 50 can be determined for each depth D as a depth profile of the coating 50 by depth direction analysis using X-ray photoelectron spectroscopy (XPS). In comparing the electrolyte interface side region δ1 with the active material surface side region δ2, the sulfur content α determined for each depth D of the coating 50 is calculated using the total value contained in the electrolyte interface side region δ1 and the total value contained in the active material surface side region δ2.

[0027] That is, the ratio of the sulfur component amount α contained in the active material surface side region δ2 to the sulfur component amount α contained in the electrolyte interface side region δ1 is defined as the sulfur component amount ratio R. Furthermore, the total value of the sulfur component amounts α contained in the electrolyte interface side region δ1 is defined as "α1", and the total value of the sulfur component amounts α contained in the active material surface side region δ2 is defined as "α2". Thus, the sulfur component amount ratio R based on the electrolyte interface side region δ1 can be calculated by the following formula.

[0028] R = α2 / α1 (1) More specifically, in the secondary battery 1 of this embodiment, lithium fluorosulfate and lithium methanesulfonate are used as the sulfur-based additive 60 contained in the electrolyte 45. The secondary battery 1 of this embodiment is configured such that the ratio of the amount of sulfur component α contained in the active material surface side region δ2 to the amount of sulfur component α contained in the electrolyte interface side region δ1 is controlled by adjusting the amounts of these additives, as described above.

[0029] (action) That is, when comparing reduction potentials, lithium methanesulfonate has a higher reduction potential than lithium fluorosulfonate. Therefore, by adding a larger amount of lithium methanesulfonate, which has a higher reduction potential, to the electrolyte 45, the amount of sulfur component α contained in the active material surface side region δ2 increases. This makes it possible to control the ratio of the amount of sulfur component α contained in the active material surface side region δ2 to the amount of sulfur component α contained in the electrolyte interface side region δ1.

[0030] Next, the effects of this embodiment will be described. (1) A secondary battery 1 having a configuration as a lithium ion secondary battery includes an electrode sheet 35N as a negative electrode plate 52N having a negative electrode active material layer 32N laminated on a substrate 36N and a coating 50 covering a surface 32s of the negative electrode active material layer 32N. The electrolyte 45 impregnated in the negative electrode plate 52N contains a sulfur-based additive 60. Furthermore, a thickness region δ in the coating 50 from the electrolyte interface 50s to a depth D of 5 nm is defined as an electrolyte interface side region δ1, and a thickness region δ deeper than the electrolyte interface side region δ1 is defined as an active material surface side region δ2. In the secondary battery 1, the ratio of the sulfur component amount α contained in the active material surface side region δ2 to the sulfur component amount α contained in the electrolyte interface side region δ1 is 0.58 or more and 0.84 or less.

[0031] According to the above-mentioned configuration, the coating 50 contains the sulfur component S, which can enhance the effect of improving the battery performance. In particular, the rate of deterioration of the battery capacity can be reduced. As a result, the secondary battery 1 can be used for a longer period of time.

[0032] (2) The secondary battery 1 contains lithium fluorosulfonate and lithium methanesulfonate in the electrolyte 45 as the sulfur-based additive 60 . That is, by adding sulfur-based additives 60 having different reduction potentials to the electrolyte 45 and adjusting the amounts of these additives, it is possible to easily control the ratio of the amount of sulfur component α contained in the active material surface side region δ2 to the amount of sulfur component α contained in the electrolyte interface side region δ1. This allows the ratio of the amount of sulfur component α contained in the electrolyte interface side region δ1 and the active material surface side region δ2 to be set in a suitable range, thereby improving the battery performance.

[0033] The above embodiment can be modified as follows: The above embodiment and the following modifications can be combined with each other to the extent that no technical contradiction occurs.

[0034] In the above embodiment, the ratio of the sulfur component amount α contained in the active material surface side region δ2 to the sulfur component amount α contained in the electrolyte interface side region δ1 is defined as the sulfur component amount ratio R, and this sulfur component amount ratio R is set to be 0.58 or more and 0.84 or less. However, this is not limited, and it is more preferable that the sulfur component amount ratio R is 0.65 or more and 0.75 or less. Furthermore, it is more preferable that the sulfur component amount ratio R is close to 0.7, which is the intermediate value of the preferable range shown above. This can provide a more significant improvement effect on battery performance.

[0035] The sulfur component ratio R may be changed as desired within a range where the effect of improving the battery performance is recognized. For example, the preferable range of the sulfur component ratio R may be expanded to about 0.52 or more and 0.9 or less.

[0036] The thickness d of the coating 50 is arbitrary. In the above embodiment, the electrolyte 45 contains lithium fluorosulfonate and lithium methanesulfonate as the sulfur-based additive 60. The sulfur component amount ratio R of the active material surface side region δ2 to the electrolyte interface side region δ1 is controlled by adjusting the amount of these additives. However, the present invention is not limited to this, and the sulfur component amount ratio R may be set within the above preferred range by using other methods.

[0037] For example, when the assembled secondary battery 1 is initially charged to form a coating 50 on the surface 32s of the negative electrode active material layer 32N, the amount of sulfur component α contained in the active material surface side region δ2 may be increased by controlling the applied voltage.

[0038] That is, when performing such a so-called "conditioning charge", the voltage applied to the negative electrode 4 is changed in a stepwise manner. Furthermore, one of the stepwise changed applied voltages is set to a voltage lower than the reduction potential of the sulfur component S, that is, "5V", for example, about "4.0V" to "4.5V". Then, by setting the charging time for this specific voltage application step to be long, the amount α of the sulfur component contained in the active material surface side region δ2 can be increased. Even if such a configuration is adopted, the same effect as the above embodiment can be obtained.

[0039] Furthermore, the type of sulfur-based additive 60 contained in the electrolytic solution 45 may also be changed as desired. Specifically, methanesulfonic acid, trifluoromethanesulfonic acid, trienesulfonic acid, camphorsulfonic acid, etc. may be used. It is preferable to include at least one of these. In addition, cyclic sulfonic acid esters, chain sulfonic acid esters, cyclic disulfonic acid anhydrides, cyclic sulfonic acid carboxylic acid anhydrides, etc. may be used.

[0040] In the above embodiment, the electrode body 10 has a configuration as a wound body, but the positive and negative electrode sheets 35P, 35N stacked with the separator 5 sandwiched therebetween do not necessarily have to be wound. That is, the shape of the negative electrode plate is arbitrary. And, the secondary battery 1 to which this negative electrode plate is applied does not necessarily have to be a lithium ion secondary battery, and may be applied to other nonaqueous electrolyte secondary batteries.

[0041] The terminal shapes of the positive electrode terminal 38P and the negative electrode terminal 38N are not limited to the shapes shown in Fig. 1 and may be changed as desired. The shape of the case 20 that defines the outer shape of the secondary battery 1 is also not necessarily limited to a flat rectangular box shape and may be changed as desired, for example, to a cylindrical shape.

[0042] (Additional Note) Next, the technical ideas that can be understood from the above embodiment and modified examples will be described. (i) The ratio of the amount of sulfur contained in the active material surface side region to the amount of sulfur contained in the electrolyte interface side region is 0.65 or more and 0.75 or less.

[0043] (b) The sulfur-based additive contains at least one of methanesulfonic acid, trifluoromethanesulfonic acid, trienesulfonic acid, and camphorsulfonic acid.

[0044] (C) A negative electrode plate for a secondary battery, comprising a negative electrode active material layer laminated on a substrate, and an electrolyte impregnated into the negative electrode active material layer contains a sulfur-based additive, wherein in a state in which a coating covering the negative electrode active material layer is formed by charging the secondary battery, a thickness region in the coating from an electrolyte interface to a depth of 5 nm is defined as an electrolyte interface side region, and the thickness region deeper than the electrolyte interface side region is defined as an active material surface side region, and the ratio of the amount of sulfur component contained in the active material surface side region to the amount of sulfur component contained in the electrolyte interface side region is 0.58 or more and 0.84 or less. EXAMPLES

[0045] Examples will be described below to more specifically explain the configuration and effects of the present invention, but the present invention is not limited to these examples. FIG. 6 is a table showing the results of the performance test performed on the secondary battery 1. In this performance test, the secondary battery 1 also contains two types of sulfur-based additives 60 with different reduction potentials in its electrolyte 45. Specifically, "lithium fluorosulfate" was used as "additive A" with a low reduction potential. Also, "lithium methanesulfonate" was used as "additive B" with a high reduction potential. Then, by changing the amount of "additive A" and "additive B" added to the electrolyte 45, four test specimens of "Level 1" to "Level 4" with different distributions of the sulfur component S contained in the coating 50 were obtained.

[0046] More specifically, as shown in FIG. 7, in this performance test, the thickness region δ in the coating 50 from the electrolyte interface 50s to a depth D of 5 nm was defined as the electrolyte interface side region δ1, and the thickness region δ deeper than the electrolyte interface side region δ1 was defined as the active material surface side region δ2. The thickness d of the coating 50 was "60 nm". Furthermore, by performing a depth direction analysis using X-ray photoelectron spectroscopy (XPS), the sulfur component amount α of the coating 50 was measured for each depth D in the form of a so-called depth profile as shown in FIG. 7. The ratio of the sulfur component amount α contained in the active material surface side region δ2 to the sulfur component amount α contained in the electrolyte interface side region δ1 was defined as the sulfur component amount ratio R. The calculation formula is the above formula (1).

[0047] Specifically, as shown in FIG. 6, for the test specimen of "Level 1", only "Additive A" was added to the electrolyte 45 at "0.75 wt%" to obtain a coating 50 with a sulfur component ratio R of "0.52". For the test specimen of "Level 2", "Additive A" was added at "0.42 wt%" and "Additive B" was added at "0.14 wt%" to obtain a coating 50 with a sulfur component ratio R of "0.58". For the test specimen of "Level 3", "Additive A" was added at "0.45 wt%" and "Additive B" was added at "0.24 wt%" to obtain a coating 50 with a sulfur component ratio R of "0.92". For the test specimen of "Level 4", "Additive A" was added at "0.86 wt %" and "Additive B" was added at "0.4 wt %" to the electrolyte 45, thereby obtaining a coating 50 having a sulfur component ratio R of "1.06".

[0048] In addition, as an evaluation index of battery performance, a storage deterioration test was performed on each of the test specimens of "Level 1" to "Level 4" to measure their "capacity retention rate (%)". Specifically, the initial battery capacity was measured by charging and discharging each test specimen assembled as a secondary battery 1. The coating 50 of each test specimen is mainly formed during the first charge in this process, that is, during the so-called "conditioning charge". Next, each of these test specimens is stored for a certain period of time under predetermined storage conditions. As the storage conditions, the storage temperature was set to "75°C" and "SOC 80%". The storage period was set to "120 days". After the storage period, the battery capacity after storage was measured. Then, the "capacity retention rate" was obtained for each of the test specimens of "Level 1" to "Level 4" by comparing the change in battery capacity before and after storage.

[0049] Furthermore, the "capacity degradation rate" of each of these test specimens was calculated by taking "Level 1" of these test specimens as the standard "100". That is, this "capacity degradation rate" is a value calculated based on the "capacity maintenance rate" measured for each of the test specimens of "Level 1" to "Level 4" as described above. Then, these "capacity maintenance rate" and "capacity degradation rate" were used as evaluation indexes of battery performance to compare each of the test specimens of "Level 1" to "Level 4".

[0050] As shown in Figure 8, when comparing the "capacity retention rate" of each test specimen of "Level 1" to "Level 4," the largest "capacity retention rate," that is, the best result, was obtained in the test specimen of "Level 2." The "capacity retention rates" of each test specimen were 85.2%, 85.8%, 84.6%, and 81.4%, in the order of "Level 1" to "Level 4," respectively.

[0051] 9, the test results of the "capacity degradation rate" were plotted on an orthogonal coordinate system with the sulfur component amount ratio R on the horizontal axis (x-axis) and the "capacity degradation rate" on the vertical axis (y-axis). Based on this, the effect of improving the battery performance according to the distribution of the sulfur component S contained in the coating 50 was considered.

[0052] More specifically, by plotting the test results for each of the test specimens of "Level 1" to "Level 4" on the orthogonal coordinates as described above, a quadratic approximation equation was obtained that shows the relationship between the sulfur component amount ratio R and the "capacity deterioration rate" (y=ax^2+bx+c). In the equation, "^2" means "squared." In addition, in FIG. 9, this quadratic approximation equation is shown as a curve Q. It was thus confirmed that there exists a suitable range for the sulfur component amount ratio R for the effect of improving battery performance according to the distribution of the sulfur component S contained in the coating 50.

[0053] Specifically, in the above quadratic approximation formula showing the relationship between the sulfur component ratio R and the "capacity degradation rate", "a" is "364.4", "b" is "-515.6", and "c" is "269.8". As a result, the position of the "x coordinate" that is the apex of the above quadratic approximation formula is "0.71". As a result, the closer the sulfur component ratio R is to "0.71", the slower the "capacity degradation rate" becomes. In other words, it was confirmed that more favorable results were obtained.

[0054] Furthermore, since the best "capacity deterioration rate" was obtained for the "level 2" test specimen among the "level 1" to "level 4" test specimens, it is considered that the sulfur component ratio R for this "level 2" test specimen is within the preferable range. This leads to "0.58 or more" as one value that defines the preferable range of the sulfur component ratio R.

[0055] Moreover, according to the above quadratic approximation, even when the sulfur component amount ratio R is "0.84", a "capacity deterioration rate" approximately equal to that of the "Level 2" test specimen is obtained. This leads to "0.84 or less" as one value that defines the preferable range of the sulfur component amount ratio R. From the above results, it was confirmed that in order to reduce deterioration of the battery capacity, it is preferable that the ratio of the sulfur component amount α contained in the active material surface side region δ2 to the sulfur component amount α contained in the electrolyte interface side region δ1 is 0.58 or more and 0.84 or less.

[0056] Furthermore, by setting the upper and lower limits of the preferred range of the sulfur component ratio R close to "0.71", which is the apex of the quadratic approximation formula, a more suitable effect of reducing battery capacity degradation can be obtained. As a result, it is presumed that it is more preferable for the ratio of the sulfur component amount α contained in the active material surface side region δ2 to the sulfur component amount α contained in the electrolyte interface side region δ1 to be, for example, 0.65 to 0.75.

[0057] In addition, if the test specimen of "Level 1" as a reference has a "capacity degradation rate" equivalent to that of the conventional technology, the value of the sulfur component ratio R in the test specimen of "Level 1" leads to "0.52 or more" as one value that defines the preferable range of the sulfur component ratio R. Furthermore, according to the above-mentioned quadratic approximation formula, even when the sulfur component ratio R is "0.9", a "capacity degradation rate" approximately equal to that of the test specimen of "Level 1" is obtained, and thus "0.9 or less" is derived as one value that defines the preferable range of the sulfur component ratio R. From the above results, it is presumed that it is also possible to expand the preferable range of the sulfur component ratio R to 0.52 or more and 0.9 or less in order to reduce the degradation of the battery capacity. [Explanation of symbols]

[0058] 1…Secondary battery 32N…Negative electrode active material layer 32s…Surface 35N…Electrode sheet 36N…Base material 45...Electrolyte 50...Coating 50s…electrolyte interface 52N…Negative electrode plate 60...Sulfur-based additives D…Depth δ…Thickness region δ1…electrolyte interface side area δ2…Active material surface side region α: Sulfur content

Claims

1. A secondary battery comprising a negative electrode plate having a negative electrode active material layer laminated on a substrate and a coating covering a surface of the negative electrode active material layer, the secondary battery comprising: an electrolyte impregnated in the negative electrode plate, the electrolyte including a sulfur-based additive; A thickness region of the coating film from the electrolyte interface to a depth of 5 nm is defined as an electrolyte interface side region, and the thickness region deeper than the electrolyte interface side region is defined as an active material surface side region, A secondary battery, wherein the ratio of the amount of sulfur contained in the active material surface side region to the amount of sulfur contained in the electrolyte interface side region is 0.58 or more and 0.84 or less.

2. 2. The secondary battery according to claim 1, wherein the sulfur-based additive comprises lithium fluorosulfonate and lithium methanesulfonate.

Citation Information

Patent Citations

  • Nonaqueous electrolyte secondary battery and manufacturing method of the battery

    JP2014127313A

  • Secondary battery

    WO2022059557A1